2013
DOI: 10.3109/13813455.2013.774022
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone induces the Wnt signalling pathway in 3T3-L1 adipocytes

Abstract: Synthetic glucocorticoids are potent anti-inflammatory drugs but show dose-dependent metabolic side effects such as the development of insulin resistance and obesity. The precise mechanisms involved in these glucocorticoid-induced side effects, and especially the participation of adipose tissue in this are not completely understood. We used a combination of transcriptomics, antibody arrays and bioinformatics approaches to characterize prednisolone-induced alterations in gene expression and adipokine secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
(103 reference statements)
0
8
1
Order By: Relevance
“…This raised the possibility that the synergy between pitavastatin and prednisolone occurred as a result of prednisolone-induced changes in gene expression. Previous work 33 has identified genes whose expression is altered in 3T3-L cells exposed to prednisolone, including some which form part of the mevalonate pathway. The expression of the genes encoding HMGCR, geranylgeranyl transferase I and II (GGTI, GGTII), isopentenyl diphosphate isomerase (IDI1), mevalonate decarboxylase (MVD) and farnesyl diphosphate synthase (FDPS) were reported to be decreased in cells exposed to prednisolone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This raised the possibility that the synergy between pitavastatin and prednisolone occurred as a result of prednisolone-induced changes in gene expression. Previous work 33 has identified genes whose expression is altered in 3T3-L cells exposed to prednisolone, including some which form part of the mevalonate pathway. The expression of the genes encoding HMGCR, geranylgeranyl transferase I and II (GGTI, GGTII), isopentenyl diphosphate isomerase (IDI1), mevalonate decarboxylase (MVD) and farnesyl diphosphate synthase (FDPS) were reported to be decreased in cells exposed to prednisolone.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the mechanism by which prednisolone was synergistic with pitavastatin in more detail, levels of mevalonate pathway enzymes were investigated by immunoblotting. An earlier study found that prednisolone altered the expression of genes encoding several mevalonate pathway enzymes including HMGCR, GGTI, GGTII, IDI1, MVD and FDPS 33 . Inhibiting the mevalonate pathway by two separate mechanisms provides a potential rationale to explain the synergy we observed between pitavastatin and prednisolone.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the action of glucocorticoids through their cognate receptor, specific pathways can be impacted by and can mediate glucocorticoids effects 24 . In order to understand leptin expression mechanisms in dedifferentiated OA chondrocytes, we searched for signalling pathways impacted by prednisolone.…”
Section: Leptin Expression In Normal and Oa Hip Cartilagementioning
confidence: 99%
“…Further studies are necessary to validate this hypothesis. Regulation of TGFb and Wnt/b-catenin pathways by glucocorticoids was already reported but its precise impact is not clearly defined 24 . Here we propose glucocorticoids as inducers of TGFb and Wnt/b-catenin signalling pathways to enhance leptin production.…”
Section: Bmentioning
confidence: 99%
“…These rats also exhibit increased mRNA and protein content of adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) in the epididymal tissue [10] . In differentiated 3T3L-1 cells, IRS-1 Tyr phosphorylation and PKB activity are also impaired by prednisolone [19] and dexamethasone [20] treatment. The exact mechanisms by which GCs attenuate the main insulin signaling components (e.g., IRSs and PKB proteins) are not well established.…”
Section: Research Highlightmentioning
confidence: 99%